The Effect of Lower Body Anaerobic Pre-loading on Upper Body Ergometer Time Trial Performance - Priit Purge; Dmitri Valiulin; Allar Kivil; Alexander Müller; Gerhard Tschakert; Jaak Jürimäe; Peter Hofmann (MDPI AG, 2021)
Pre-competitive conditioning has become a substantial part of successful performance. In addition to temperature changes, a metabolic conditioning can have a significant effect on the outcome, although the right dosage of such a method remains unclear. The main goal of the investigation was to measure how a lower body high-intensity anaerobic cycling pre-load exercise (HIE) of 25 s affects cardiorespiratory and metabolic responses in subsequent upper body performance. Thirteen well-trained college-level male cross-country skiers (18.1 ± 2.9 years; 70.8 ± 7.6 kg; 180.6 ± 4.7 cm; 15.5 ± 3.5% body fat) participated in the study. The athletes performed a 1000-m maximal double-poling upper body ergometer time trial performance test (TT) twice. One TT was preceded by a conventional low intensity warm-up (TTlow) while additional HIE cycling was performed 9 min before the other TT (TThigh). Maximal double-poling performance after the TTlow (225.1 ± 17.6 s) was similar (p > 0.05) to the TThigh (226.1 ± 15.7 s). Net blood lactate (La) increase (delta from end of TT minus start) from the start to the end of the TTlow was 10.5 ± 2.2 mmol L−1 and 6.5 ± 3.4 mmol L−1 in TThigh (p < 0.05). La net changes during recovery were similar for both protocols, remaining 13.5% higher in TThigh group even 6 min after the maximal test. VCO2 was lower (p < 0.05) during the last 400-m split in TThigh, however during the other splits no differences were found (p < 0.05). Respiratory exchange ratio (RER) was significantly lower in TThigh in the third, fourth and the fifth 200 m split. Participants individual pacing strategies showed high relation (p < 0.05) between slower start and faster performance. In conclusion, anaerobic metabolic pre-conditioning leg exercise significantly reduced net-La increase, but all-out upper body performance was similar in both conditions. The pre-conditioning method may have some potential but needs to be combined with a pacing strategy different from the usual warm-up procedure.